The role of traditional and new international relations actors in addressing climate change - Shevchenko, Olena (Eastern Review, 2019)
Addressing global climate change brings up a number of priority issues. The fundamental issue is the definition of the participants in this process and the scope of their competencies and areas of responsibility. Practice shows that modern global challenges, which include global climate change, cannot be solved individually and in a straightforward manner without the involvement of all stakeholders and the general public. The article discusses actions aimed at adapting and mitigating the consequences of global climate challenges carried out by states and their alliances (as traditional international actors) and corporations and media (as new international actors). It is shown that today state political decisions on the adaptation to and mitigation of the consequences of global climate change are associated, in particular, with the transition to a low-carbon economy. At the same time, specific and effective climate policies are also being implemented by international corporations. Global media implement their own climate initiatives from one side and shape international public opinion regarding the climate challenge from the other side. The author concludes that, despite the active presence of the theme of global climate change in international and national political discourse, as well as in media and in the social and economic projects of corporations, the general attempts to resolve the issue can’t be considered as a well coordinated, and the results are not efficient enough.